Molecular evidence for an Andean origin and a secondary gene pool for the lima bean (Phaseolus lunatus L.) using chloroplast DNA - Fofana, B.; Baudoin, Jean-Pierre; Vekemans, X; Debouck, Daniel G.; Jardin, Paul du (Springer, 1999)
Chloroplast DNA (cpDNA) diversity has been examined using PCR-RFLP and RFLP strategies for phylogenetic studies in the genus Phaseolus. Twenty-two species, including 4 of the 5 cultivated species (P. lunatus L., the Lima bean; P. vulgaris L., the common bean; P. coccineus L., the runner bean and P. polyanthus Greenman, the year-bean), represented by 86 accessions were included in the study. Six PCR primers designed from cpDNA and a total cpDNA probe were used for generating markers. Phylogenetic reconstruction using both Wagner parsimony and the neighbor-joining method was applied to the restriction fragment data obtained from each of the molecular approaches. P. vulgaris L. was shown to separate with several species of largely Mesoamerican distribution, including P. coccineus L. and P. polyanthus Greenman, whereas P. lunatus L. forms a complex with 3 Andean species (P. pachyrrhizoides Harms, P. augusti Harms and P. bolivianus Piper) co-evolving with a set of companion species with a Mesoamerican distribution. Andean forms of the Lima bean are found to be more closely related to the 3 Andean wild species than its Mesoamerican forms. An Andean origin of the Lima bean and a double derivative process during the evolution of P. lunatus are suggested. The 3 Andean species are proposed to constitute the secondary gene pool of P. lunatus, while its companion allies of Mesoamerican distribution can be considered as members of its tertiary gene pool. On the basis of these data, an overview on the evolution of the genus Phaseolus is also discussed.